Brainstorming Features in LMS (BRAIN.PAI) and its Effect on Student Learning Interest - Fitra Zahrotul Luqmi; Agus Pahrudin; Imam Syafe’i; Teguh Setia Isma Ramdan (Didaktika Religia, 2025)
The development of a Learning Management System (LMS)-based application with the research objective of analyzing the impact of the brainstorming method by substantially sparking student learning interest in Islamic Religious Education (PAI) learning at the junior high school level in Bandar Lampung City. The LMS application named BRAIN.PAI is expected to facilitate a more interactive and effective learning process, while the analysis of the impact of brainstorming aims to understand how this method can increase student engagement and interest in learning. This study adopted a structured Research and Development (R&D) approach, with the ADDIE development model as its main framework (Analysis, Design, Development, Implementation, and Evaluation). The main objectives are to create a functional LMS application and assess the effect of brainstorming in increasing student interest and engagement. In the analysis phase, LMS and brainstorming needs are identified. The design phase includes designing the LMS structure and brainstorming flow. Development involves building an application with brainstorming features. Implementation trials of the LMS with eighth-grade students, followed by evaluation of feasibility, practicality, and effectiveness through validation, questionnaires, tests, and observations. The results of the study indicate that the developed LMS is feasible, practical, and effective.